1960
DOI: 10.1111/j.1365-2672.1960.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Studies of the Colony Count Technique for Soil Bacteria

Abstract: SUMMARY: A series of co‐operative experiments was conducted to compare the bacterial colony counts of soil obtained by workers in different laboratories, using soil extract agar and other media for the determinations. In the earlier experiments it was not possible to obtain a reasonable degree of reproducibility of results between laboratories even when the plating technique was carefully prescribed. By modification and more rigid standardization of the technique closer agreement was obtained in subsequent ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1964
1964
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Contudo, em momento algum houve proporcionalidade entre as diluições, como teoricamente deveria ocorrer. Porém, estas diferenças eram esperadas, uma vez que Egdell et al (1960) também não encontraram relações proporcionais entre diluições 10 -5 e 10 -6 , que foram de 1,5 a 2 vezes. Assim, estes autores citam que partículas de solo, agregados de células e diferenças de microlitros na diluição poderiam compor uma hipótese provável para a não observação de proporcionalidade entre as diluições.…”
Section: Resultsunclassified
“…Contudo, em momento algum houve proporcionalidade entre as diluições, como teoricamente deveria ocorrer. Porém, estas diferenças eram esperadas, uma vez que Egdell et al (1960) também não encontraram relações proporcionais entre diluições 10 -5 e 10 -6 , que foram de 1,5 a 2 vezes. Assim, estes autores citam que partículas de solo, agregados de células e diferenças de microlitros na diluição poderiam compor uma hipótese provável para a não observação de proporcionalidade entre as diluições.…”
Section: Resultsunclassified
“…Frequently, the higher the dilution, the greater the final counts (Meiklejohn 25; Egdell et al 10; Jensen 2o). In some experiments a statistically significant regression coefficient may be obtained at one dilution but not at another.…”
Section: T H E D a T A P L O T T E D In Figs I To 3 Show T H A T If mentioning
confidence: 97%
“…The latter was found to be slightly bettet than the other two and considered to be quite satisfaetory. Other diluents are recommended in the literature such as Ringer's solution (Egdell et al 10) and sodium pyrophosphate solution (Augier and Lavergne 1). With respect to the latter, Jensen 20 has reported that, while sodium pyrophosphate increased the dispersion of the cells, it had an injurious effect on miero-organisms; an observation recently confirmed by Gray and Hill 15, who have made a careful comparison of various diluents including sodium pyrophosphate.…”
Section: T H E D a T A P L O T T E D In Figs I To 3 Show T H A T If mentioning
confidence: 99%
“…The limitations of determining bacterial or fungal cfu that are representative of microbial communities by plate counts have been examined by numerous researchers (Butterfield 1932, Egdell et al 1960, Gossling 1958, Jensen 1962, Skinner et al 1952, Weiringa 1958; the general consensus is that plate counts are by no means quantitative for the total microbial community and only represent a fraction of the total. Moreover, this fraction also does not represent an absolute value but a relative value dependent on well controlled and reproducible laboratory techniques, as well as the composition of the plating media.…”
Section: Discussionmentioning
confidence: 99%
“…The use of plate count techniques in estimating bacteria communities in soil have been critically evaluated by numerous researchers (Butterfield 1932, Skinner 1952, Weiringa 1958, Gossling 1958, Egdell et al 1960, Jensen 1962. A primary criticism concerns the inability to measure the total bacterial community in soil using a given growth medium because a given growth medium is selective for certain bacteria present.…”
Section: Field Studiesmentioning
confidence: 99%